2016
DOI: 10.2147/dddt.s121630
|View full text |Cite
|
Sign up to set email alerts
|

Use of bedaquiline and delamanid in diabetes patients: clinical and pharmacological considerations

Abstract: Antituberculosis (anti-TB) treatment may be affected by both diabetes and hypoglycemic agents in patients with these 2 comorbidities. However, data supporting this conclusion relate only to standard anti-TB therapies. Sirturo® (bedaquiline) and Deltyba® (delamanid), novel drugs for multidrug-resistant tuberculosis (MDR-TB), are recommended for diabetes patients when another effective treatment regimen cannot be provided. Currently, there are no clinical data related to the use of these agents in diabetes patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…It is widely accepted that metformin and insulin analogues used to control high blood glucose levels also possess anti-inflammatory properties that render these hypoglycemic agents useful for treating severe infections, such as MDR/XDR-TB with comorbid DM [ 17 ]. Indeed, the inclusion of insulin and metformin or both agents in treatment regimens for the vast majority of patients with DM has likely already benefited patients afflicted with both MDR/XDR-TB and DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that metformin and insulin analogues used to control high blood glucose levels also possess anti-inflammatory properties that render these hypoglycemic agents useful for treating severe infections, such as MDR/XDR-TB with comorbid DM [ 17 ]. Indeed, the inclusion of insulin and metformin or both agents in treatment regimens for the vast majority of patients with DM has likely already benefited patients afflicted with both MDR/XDR-TB and DM.…”
Section: Discussionmentioning
confidence: 99%
“…BDQ is metabolized primarily through hepatic metabolic pathways that are shared with several oral hypoglycemic agents (e.g., thiazolidinedione, acarbose); thus, hepatic-related adverse reactions may develop more frequently when BDQ and hypoglycemic agents are used together [ 17 ]. Consequently, here 38.3% of patients with MDR/XDR-TB and DM reported incidents of hepatotoxicity manifesting primarily as liver enzyme (AST/ALT) elevations, significantly more than the non-DM group rate (16.8%) ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“… 33 Moreover, there may be enhanced risk of QT prolongation by bedaquiline if a CYP3A4 inhibitor like bromocriptine (recommended adjunct therapy for glycemic control) is used for diabetic patients under antidiabetic drugs like sulfonylureas therapy. 34 Dosage adjustment may be required for anti-TB oral therapy with bedaquiline in diabetic conditions. The present findings are based on the pharmacokinetic study after single dose oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of DM comorbidity to unfavourable treatment of TB, none of the TB trials that included DM comorbidity reported specific outcomes related to the TB‐DM subpopulation. A systematic review suggested a phase III clinical trial to ensure the safe use of new TB drugs in diabetes patients . Indeed, there is still a lack of sufficient data regarding pharmacokinetic and clinical data of TB drugs in DM patients, despite the continuous growth of DM patients in the future that will cause a further threat to TB control.…”
Section: Discussionmentioning
confidence: 99%